ORCHIDS - Heira Vanessa, Nelson; Meekiong, Kalu (UNIMAS Publisher, Sarawak Forestry Corporation and Natural History Publications (Borneo) Sdn. Bhd., 2025)
Orchids, belonging to the family Orchidaceae, are a remarkable group of flowering plants, primarily found in tropical regions that are characterized by high annual precipitation and minimal seasonal variation. Renowned for their floral diversity and unique forms, orchids are among the most advanced of monocotyledons. Malaysia is particularly rich in orchid species, with an estimated 972 species in Peninsular Malaysia and approximately 3,000 species in Borneo. These plants exhibit two growth patterns — sympodial and monopodial — and can thrive in terrestrial, epiphytic, lithophytic and saprophytic habitats. The island, with 10% of the world’s total, is considered a centre of diversity for the group.